ADVOCATION AND FACILITATION TO ESTABLISH A PARTICIPATORY VILLAGE REGULATIONS IN NGROTO VILLAGE, MALANG REGENCY - Damayanti, Galieh; Indra Rahmawan, Triya; Saraswati, Destriana; Rohma Rozikin, Mokhamad (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
This community service program in Ngroto Village, Pujon District, Malang Regency aims to increase community understanding and skills in formulating rules for participating villages. This activity was launched to follow up on the results of a previous study on the obstacles to village code formation. In principle, the formation of a village order in Ngroto Village follows the path specified in Permendagri No. 111 of 2014 from the Technical Guidelines for the Village Law, however, sometimes the process of forming the village order encounters obstacles. The obstacles that arise are: (1) the identification of opportunities and problems as outlined in the draft village regulations is not precise, detailed and complete; (2) lack of direct participation from some communities in drafting village regulations; (3) the process of drafting village regulations took longer during the Covid-19 pandemic; (4) lack of socialization and knowledge of village officials' projects; and (5) the lack of dissemination of village regulations which were transferred to the RT/RW level. This non-profit activity is carried out through advocacy and facilitation methods. Finally, an ideal village can be created through optimal community participation in the village development process, where the village government leadership responds to the wishes and aspirations of the village community.